Effect of energy level during late gestation on the performance of heifers calving for the first time (3 year summary) - Corah, L.R.; Fleck, A.; McKee, M.; Schalles, R.R. (Kansas State University. Agricultural Experiment Station, 2011)
Effect of varying energy levels fed during gestation on reproduction and calf performance were studied in three trials involving 266 first calf heifers. Reducing energy during mid-gestation did not adversely affect the performance of the heifers when they were fed properly for at least 50 days before calving. Heifers on restricted levels of energy during mid-gestation and then elevated tended to have both higher first-service conception rates and total conception rates. Restricting energy throughout the gestation period reduced reproductive performance, causing lighter calves at birth and weaning emphasizing the importance of energy in the diet of first calf heifers.
Cattlemen's Fate in '78 is known as Cattlemen’s Day, 1978
Keywords: Beef; Energy; Performance; Conception rates